A história de Antoine Doinel: um estudo sobre a formação - Braga, Ive (2012)
The following research analises the individual formation s process during its trajectory in the institutions. In order to do that, were taking in consideration as sources of information and analized excerpts of five films made by the french director François Truffaut, namely: The Four Hundred Blows (1959), Antoine and Colette (1962), Stolen Kisses (1968), Bed and Board (1970), Love on the Run (1979). They portray the story of Antoine Doinel autobiographical character who stars these series of films lived among different institutions: Family, school, reformatory, prison, army and other groups responsible for his socialization. With the purpose of exploring the formation of the individual in its objectivation in the work of art, the theoretical framework adopted to build this study is The Critical Theory of Society, using, mainly, the concepts of individual, family, society, formation and so-called formation developed by Theodor W. Adorno and Max Horkheimer. The society objectvated in the work of art has allowed the investigation to find that the individual cannot exist in the society accordind to its self-determination. The formation by means of institutions is permeated by impoverished experiencies based in punishing and coercive methods that aim the standardization to the stablished order and social control, enforcing deep marks in the individual who has little alternatives to resist to the rules formerly determined by the suprastructure. Such appropriation of the individual in the social relationships of domination reproduces the characteristics of culture in the managed society: the so-called formation. The refusal of Antoine Doinel in adhering to the forms established by society reflects a negative relationship with the existing reality, poiting to the possibility of overcoming it